2021
DOI: 10.1097/md.0000000000026985
|View full text |Cite
|
Sign up to set email alerts
|

Safety of transrectal ultrasound-guided prostate biopsy in patients receiving aspirin

Abstract: Background: The management of aspirin before transrectal prostate puncture-guided biopsy continues to be controversial. The conclusions in newly published studies differ from the published guideline. Therefore, an updated meta-analysis was performed to assess the safety of continuing to take aspirin when undergoing a transrectal ultrasound-guided prostate biopsy (TRUS-PB). Methods: We searched the following databases for relevant literature from their inception to Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…This is supported by a recent meta-analysis, that reported no increased risk of hematuria after a prostate biopsy. However, a risk of postoperative rectal bleeding was reported [ 23 ]. Transurethral resections of bladder tumors have been reported to be safe concerning bleeding, as a previous retrospective cohort study found no increased risk of severe bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent meta-analysis, that reported no increased risk of hematuria after a prostate biopsy. However, a risk of postoperative rectal bleeding was reported [ 23 ]. Transurethral resections of bladder tumors have been reported to be safe concerning bleeding, as a previous retrospective cohort study found no increased risk of severe bleeding.…”
Section: Discussionmentioning
confidence: 99%